Co integrating Relation between Macroeconomic Variables and Stock Return: Evidence from Dhaka Stock Exchange (DSE) - Mohammad Bayezid Ali (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Abstract: The objective of this study is to investigate the long run equilibrium, short run dynamics adjustment as well as causal relationship between Dhaka stock Exchange (DSE) all share price index and macroeconomic variables of consumer price index (CPI), GDP, foreign remittances and import payment. This study uses cointegration test and vector error correction model (VECM) to identify long run equilibrium relationship and short run dynamics adjustment among these variables. The test result provides that variables are cointegrated and VECM provides that the system corrects its previous period’s level of disequilibrium by 5.98 percent per month. Granger causality test has also been performed to estimate causal relationship and the result shows unidirectional causality from CPI and foreign remittance to stock price and bi-directional causality between import payment and stock price but no causal relation between GDP and stock price. The results of this study have implications to investors, policy makers and academicians.